The value of diagnostic procedures for essential hypertension control after an early recovery period of hemorrhagic stroke (literature review) - Tkachyshyn , Oleksandr; Bespalova , Vladyslava (The Ukrainian Scientific Medical Youth Journal, 2024)
hemorrhagic stroke is the most severe type of stroke, which is more likely to lead to death and severe disability. Although there are many causes and risk factors for hemorrhagic stroke – both congenital and acquired, and mostly their combination – essential hypertension is the most common and leading cause of intracranial hemorrhage. This study aimed to make a comprehensive overview on the value of diagnostic procedures for essential hypertension control after an early recovery period of hemorrhagic stroke. The analyzed data were observed on PubMed and Ukrainian scientific sources concerning essential hypertension course in post-hemorrhagic stroke patients in relation to further prophylaxis in stable phase. All the observed manuscripts were published within the period 2014-2024. The focus of attention was made predominantly on the essential hypertension as the key factor for hemorrhagic stroke development. From the literature review, it could be concluded that the problem of essential hypertension control after hemorrhagic stroke is relevant today and needs a thorough solution to prevent the re-occurrence of cerebrovascular events. For a rational approach to the management of hypertensive patients with hemorrhagic stroke medical history, it would be necessary to perform a set of diagnostic procedures, which would include ultrasound examination of the major cervical arteries, echocardiography, 24-hour ambulatory blood pressure and electrocardiogram monitoring, determination of plasma cholesterol panel indices and blood coagulation tests.